HYDRAULIC CALCULATIONS OF POSTGLACIAL CONNECTIONS BETWEEN THE MEDITERRANEAN AND THE BLACK SEA - Myers P.G.; Wielki C.; Goldstein S.B.; Rohling E.J. (My University, 2003)
A series of simple hydraulic calculations has been performed to examine some of the questions associated with the reconnection of the Black Sea to the Mediterranean through the Turkish Strait System during the Holocene. Ryan et al.’s catastrophic flood scenario, whereby the erosive power of the marine in-fluxes, initiated after eustatic sea level reached the sill depth, opened up the Bosphorus, allowing saline water to pour into the Black Sea and filling it on a short time scale, is examined. The calculations show that although it might be possible to fill the palaeo-Black Sea within the order of a decade, a 1–2 year filling time scale is not physically possible. A hydraulic model is also used to examine the more traditional connection hypothesis of (near-)continuous freshwater outflow from the Black Sea, with a slowly increasing saline inflow from the Mediterranean beginning around 8–9 kyr BP. The model considers two forms for the structure of the Bosphorus: a shallow sill as seen today and a deep sill associated with no sediments filling the 100 m gorge above the bedrock in the strait. Sensitivity experiments with the hydraulic model show what possible strait geometric configurations may lead to the Black Sea reaching its present-day salinity of 18 psu. Salinity transients within the Black Sea are shown as a function of time, providing for values that can be validated against estimates from cores. To consider a deep, non-sediment-filled Bosphorus (100 m deep), the entry of Mediterranean water into the Sea of Marmara after 12.0 kyr BP is examined. A rapid entry of marine water into the Sea of Marmara is only consistent with small freshwater fluxes flowing through the Turkish Strait System, smaller than those of the present day by a factor of at least 4. Such a small freshwater flux would lead to the salinification of the Black Sea being complete by an early date of 10.2–9.6 kyr BP. Thus the possibility of a deep Bosphorus sill should be discounted.
Keywords: Black Sea; Bosphorus; Sea of Marmara; Mediterranean; Palaeoceanography; Hydraulic modelling; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен